Emergency Endovascular Repair for Acute Thoracic Aortic Syndrome - Ujihira, Kousuke; Saga, Toshihumi; Morishita, Kiyofumi; Narayama, Kohei; Baba, Toshio; Shibata, Go; Mawatari, Touru (Japanese Journal of Vascular Surgery, 2013)
Background: Acute thoracic aortic syndrome confers a significantly increased risk of adverse outcome and death. Endovascular treatment for such critically ill patients is expected to decrease procedural mortality and morbidity. The aim of this study was to evaluate the effect of endovascular repair on mid-term survival and outcome. Methods: From December 2007 to March 2013, 25 patients with acute thoracic aortic syndrome underwent thoracic endovascular aneurysm repairs (TEVAR). Operative indications were ruptured descending thoracic aortic aneurysm in 15 patients, traumatic thoracic aortic injury in 7, ruptured anastomotic aneurysm in 2, and idiopathic thoracic aortic rupture in 1. The mean American Society of anesthesiology physical status classification was 3±0.7. Five patients suffered from shock. Results: The 30-day mortality was 16% (4 of 25). The cause of death in 3 patients was multiple organ failure. One patient who had rerupture during balloon molding of the endograft died of massive exsanguination. Postoperative complications included 12 respiratory failure requiring prolonged mechanical ventilation, 3 strokes, and 2 renal failure necessitating dialysis. Endgraft-related complications were access trouble in 3 patients, endoleak in 3 patients, and graft migration in 1 patient. Of the 4 patients with endoleak or graft migration, two patients underwent reTEVAR in the follow-up. Technical success was achieved in 21 patients (84%) and clinical success at 90 days in 18 (72%). There were 5 late deaths. Aneurysm-related death occurred in 2 patients among them. Kaplan-Meier survival was 61±11% at 1 year and 54±12% at 3 years. Conclusions: Early and midterm outcomes of emergency endovascular repair for acute aortic syndrome are good when taking into account high-risk situations. However, long-term follow-up will be needed because appropriate-size stent grafts were not always used in the emergency settings.